One hundred years of Ecuadorian biomedical scientific output and its association with the main causes of mortality: a bibliometric study - Sisa, Ivan; Caicedo-Potosí, Jhon; Cordovez, María; Verdezoto, Clara; Barreno, Mishell; Coral, Martín; Herrera-Franco, Gricelda (Frontiers in Medicine, 2024)
Introduction: Historically, low-and middle-income countries have been scarce producers of biomedical research; only 2% of the global scientific output is produced by these countries despite accounting for 92% of the global burden of disease. In addition, few low-and middle-income countries have exhaustively mapped and analyzed their scientific production in health and its association with main local burden of disease.Objective: To evaluate the evolution of biomedical research in Ecuador over the last 100 years and its relationship with the main causes of mortality.Methods: A bibliometric study embedded in a systematic review design was carried out using biomedical publications indexed in Scopus and Web of Science (WoS) during the period 1920-2021. Information from the National Institute of Statistics and Census was used to identify the main causes of mortality.Results: Our search strategy identified 16,697 publications related to biomedicine in Ecuador. Of these 3,225 articles met the criteria for this study. Since 2010, there has been an exponential increase in scientific production in biomedicine. This increase was predominantly based on cross-sectional observational studies (49.67%). During the period analyzed (1920-2021), biomedical production was distributed with 52.43% in clinical research, 37.79% in public health, and 9.77% in basic sciences. The research focus with the highest number of publications was epidemiology and surveillance system of diseases (23.44%). Additionally, private universities are the largest producers of biomedical research compared to public universities, 40.12% vs. 19.60%, respectively.Of the total biomedical research produced, 18.54% is associated with the main causes of mortality, and the Ecuadorian private university is the largest contributor to these studies compared to public universities, 39.97% vs. 16.72%.In one century, Ecuador produced 3,225 articles in biomedicine, according to our criteria. 18.54% of the total produced is aimed at solving the main causes of mortality in the country. Private universities are the leaders in scientific production related to health in Ecuador.